ANALYSIS OF STRATOSPHERIC OZONE AND OZONE DEPLETION SUBSTANCES VARIABILITY IN QUALITY OF UV INDEX OVER INDONESIA RELATED TO MONTREAL PROTOCOL - AYU WULANDARI (NIM: 25316308), RIRIS
Ozone in the stratospheric layer acts as a protector of ultraviolet radiation. The use of ozone-depleting substances (ODS) in human activities has reduced the concentration of stratospheric ozone. The existence of the Montreal Protocol can control ODS production and consumption. Nonetheless, several studies suggest that stratospheric ozone concentration has not increased. ODS concentrations in the stratosphere layer (in the form of BrO and ClO) need to be observed temporally and spatially using satellite data (Microwave Limb Sounders (MLS) Aura satellite sensor) so that the scope of observation can be longer and wider. Low stratospheric ozone concentrations can result in a high UV (UVI) index. This study focused on Indonesia from January 1, 2005 to January 31, 2017, by calculating the correlation between ODS and stratospheric ozone. From the vertical profile, it was found that the maximum ozone concentration was at 10 hPa (31 km), maximum BrO concentration at 31.6 hPa (24 km), and maximum ClO concentration at 2.1 hPa (42 km). The strongest correlation between ozone and BrO (-0.58) occur at 6.8 hPa or 33.5 km. Meanwhile, the strongest correlation between ozone and ClO (-0.43) occur at 4.6 hPa or 36 km. The greatest negative correlation between UVI and stratospheric ozone (-0.5987) occurred at 1 hPa or 47.7 km. Meanwhile, the reduction in total ozone in the atmosphere affected increasing of UVI with a negative correlation of -0.25.